Beastly Tales from Here and There - Vikram Seth (Bharat Penguin Books, 2001)
From the impish to the brilliantly comic, Vikram Seth's animal fables in verse can (like Diwali sweets) be enjoyed by young and old alike. Familiar characters in a new and magical form, such as the greedy crocodile who was outwitted by the monkey or the steady tortoise who out-ran the hare, here take their place beside a newly minted gallery of characters and creatures who are quirky, comical and always fun. Of the ten tales told here, two come from India, two from China, two from Greece, two from Ukraine, and two, as the author puts it "came directly to me from the Land of Gup." This is a book that displays astonishing versatility of the poet who gave us The Golden Gate and All You Who Sleep Tonight. The flair and delight of Beastly Tales from Here and There is proof that
Keywords: Fiction -- Fiction; Short Stories -- Short Stories